Acute toxicity and sublethal effects of the mixture glyphosate (Roundup® Active) and Cosmo-Flux®411F to anuran embryos and tadpoles of four Colombian species - Henao Muñoz, Liliana Marcela (Universidad de Costa Rica, 2015)
Glyphosate is the most widely used herbicide in the world with application in agriculture, forestry, industrial weed control, garden and aquatic environments. However, its use is highly controversial for the possible impact on not-target organisms, such as amphibians, which are vanishing at an alarming and rapid rate. Due to the high solubility in water and ionic nature, the glyphosate requires of surfactants to increase activity. In addition, for the control of coca (Erythroxylum coca) and agricultural weeds in Colombia, formulated glyphosate is mixed and sprayed with the adjuvant Cosmo-Flux®411F to increase the penetration and activity of the herbicide. This study evaluates the acute toxic and sublethal effects (embryonic development, tadpole body size, tadpole swimming performance) of the mixture of the formulated glyphosate Roundup® Active and Cosmo-Flux®411F to anuran embryos and tadpoles of four Colombian species under 96h laboratory standard tests and microcosms, which are more similar to field conditions as they include soil, sand and macrophytes. In the laboratory, embryos and tadpoles of Engystomops pustulosus were the most tolerant (LC50=3 904µg a.e./L; LC50=2 799µg a.e./L, respectively), while embryos and tadpoles of Hypsiboas crepitans (LC50=2 203µg a.e./L; LC50=1 424µg a.e./L, respectively) were the most sensitive. R. humboldti and R. marina presented an intermediate toxicity. Embryos were significantly more tolerant to the mixture than tadpoles, which could be likely attributed to the exclusion of chemicals by the embryonic membranes and the lack of organs, such as gills, which are sensitive to surfactants. Sublethal effects were observed for the tadpole body size, but not for the embryonic development and tadpole swimming performance. In microcosms, no toxicity (LC50 could not be estimated), or sublethal responses were observed at concentrations up to fourfold (14.76kg glyphosate a.e./ha) the highest field application rate of 3.69kg glyphosate a.e./ha. Thus, toxicity was less in the microcosms than in laboratory tests, which may be attributed to the presence of sediments and organic matter which rapidly adsorb glyphosate and surfactants such as POEA. It is concluded that the mixture of glyphosate (Roundup® Active) and Cosmo-Flux®411F, as used in the field, has a negligible toxic effect to embryos and tadpoles of the species tested in this study. Liliana Marcela Henao Muñoz1, Claudia Marsela Montes Rojas2, Manuel Hernando Bernal Bautista3 Grupo de Herpetología, Eco-Fisiología & Etología, Departamento de Biología, Universidad del Tolima, Calle 42 Barrio Santa Helena, Ibagué, Colombia; lmhenaom@ut.edu.co1, cmmontesr@ut.edu.co2, mhbernal@ut.edu.co3